Otimização da detecção de raquitismo da soqueira e escaldadura das folhas em cana-de-açúcar utilizando PCR - DIAS, Vanessa Duarte (2012)
The sugarcane production areas are increasing in Brazil due to increased ethanol consumption by flex fuel cars. The planted area is growing, but productivity has been declining in recent years, and factors such as incidence of diseases in the crop may be contributing to this situation. Among the diseases, bacteria such as scald of the leaves and ratoon stunting disease, are of great importance to the crop because they can reduce productivity by up to 30% and the symptoms are not always displayed in the field, thus requiring advanced techniques to detect such bacterial diseases. Among the most used techniques for diagnosis serological tests are quite common, which has as main advantage the capacity of quantitative detection of the presence of bacteria in the culms. However, this detection is only possible if the bacterial title is relatively high. The PCR technique method is more sensitive for detecting low levels of bacteria in stems, but the DNA extractions should be performed in order to purify the DNA to reduce the presence of inhibitory substances in the extract. Thus in this study five different methods of DNA extraction of Xanthomonas albilineans and Leifsonia xyli subsp. xyli were tested and performed in three steps: pure bacteria, bacteria inoculated directly in the extract from five different varieties of sugarcane, and extract from a stem knowingly infected with these bacteria. The results indicate that the amplifications occur more frequently when the products and repeatability of the extractions are diluted by 10-4 in the Leaf Scald. Without this diluition steps, the amplification does not occur, even with the method of DNA extraction considered as a standard. Thus, it is concluded that the detection does not happen if the DNA extraction product is not diluted at least 1000 times, which should prevent the action of inhibitory factors that can hinder the PCR reactions. As for the ratoon stunting disease additional studies are needed to enable its detection by PCR.